Pelatihan “Remaja Jago Kelola Diri Tanpa Drama” bagi Remaja Vihara Dhamma Bhakti Tangerang (Jurnal Pelayanan Masyarakat, 2026)
This community service activity aims to improve teenagers' self-management skills through the program “Remaja Jago: Kelola Diri Tanpa Drama”. The program was specifically designed to provide a practical and applicable understanding for youth on how to recognize their own potential, manage emotions effectively, organize time efficiently, and make wise and responsible decisions in daily life. The activity was carried out at Vihara Dhamma Bhakti Tangerang with 20 participants aged 13–20 years, representing a diverse range of educational and social backgrounds. Methods included interactive lectures, engaging educational games, structured group discussions, and guided self-reflection sessions to encourage active participation and deeper personal insight. Evaluation results showed a significant improvement in participants’ decision-making abilities, personal discipline, emotional control, and goal-setting skills after completing the program. In addition, participants demonstrated increased self-confidence and awareness of their strengths and weaknesses. Overall, this program effectively contributes to developing independent, disciplined, and responsible youth character, while also equipping them with essential life skills needed to face various personal and social challenges in the future.